2019
DOI: 10.1016/j.ipej.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and usability of single-lead ECG from smartphones - A clinical study

Abstract: Background Several wireless ECG devices are commercially available for possible screening, monitoring and diagnosis of rhythms. The field is rapidly expanding, and some devices have demonstrated acceptable qualities. The objective was to evaluate the accuracy, usability and diagnostic capabilities of smartphone ECG in both patients and healthy controls. Methods We used a commercially available smartphone ECG device, connected wirelessly to a tablet, to record a 30-s lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 16 publications
3
24
5
1
Order By: Relevance
“…Moreover, two other studies in 381 and 94 subjects without known QT interval prolongation, respectively, showed relevant discrepancies in the QT interval between single lead mobile ECG devices and 12-lead ECGs. 16,17 Malone et al 13 furthermore reported that the QT interval was not measurable in 9% of their study subjects due to low T wave amplitudes. Our results expand the current knowledge and suggest, that the interpretability of the limb leads further decreases with even longer QT intervals in patients experiencing TdP.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, two other studies in 381 and 94 subjects without known QT interval prolongation, respectively, showed relevant discrepancies in the QT interval between single lead mobile ECG devices and 12-lead ECGs. 16,17 Malone et al 13 furthermore reported that the QT interval was not measurable in 9% of their study subjects due to low T wave amplitudes. Our results expand the current knowledge and suggest, that the interpretability of the limb leads further decreases with even longer QT intervals in patients experiencing TdP.…”
Section: Resultsmentioning
confidence: 90%
“…For single-lead ECG, one of these IoT-based wearable devices has shown many applications, such as the ECG-derived respiration (EDR) rate over past years, using different techniques on features, such as R-amplitude, QRS complex, RS slope, etc., which are sensitive to noise or artifacts during continuous ambulatory monitoring [ 2 ]. On the other hand, a single-lead ECG signal is one of the major candidates for promoting the opportunities of telemonitoring by measuring the heart rate, cardiac rhythm, and even detection of atrial fibrillation (AF) in chronic disease [ 3 , 4 , 5 ]. However, these devices still face some issues, such as power consumption, and a certain degree of inaccuracies, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent advances in portable and wearable medical devices may become highly useful in this premature screening of silent AF, because they are able to significantly increase the monitoring time window where the arrhythmia can be detected. Thus, fresh improvements in low-power embedded systems, communication protocols, and cloud computing technologies have allowed the development of numerous wearable systems with the ability for ECG monitoring over several weeks and even months, while the subject continues a normal active life [ 15 , 16 , 17 , 18 ]. However, these devices will usually work in highly dynamic and changing environments, thus providing ECG signals that are especially prone to be corrupted with different kinds of noises, such as motion artifacts, powerline interference, baseline wander, and high-frequency electromyography disturbances, among others [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a broad variety of techniques for ECG quality assessment have been proposed to date [ 20 ], most of them cannot deal with signals acquired via portable or wearable systems. On the one hand, many algorithms have been designed to simultaneously analyze the 12 leads found in the standard ECG, but portable and wearable systems often present a more reduced number of signals, commonly between one and three [ 15 , 16 , 17 , 18 ]. On the other hand, numerous methods raised to assess single-lead ECG quality are based on detecting fiducial points and morphological events in the signal, and then computing parameters such as mean RR interval, ratio of maximum to minimum RR interval, time consistency of PQRST waveforms, coherence of QRS complexes, etc.…”
Section: Introductionmentioning
confidence: 99%